Community perceptions of climate change, lived experiences and health in a coastal village of Odisha: a qualitative study - Reddy, Chelikam Veeraraghavendra; Nallala, Srinivas (International Journal Of Community Medicine And Public Health, 2025)
Background: Climate change poses notable risks to health and livelihoods, and overall wellbeing, particularly in coastal regions of India. Rural Coastal communities face recurring adverse climatic events that disrupt daily life, health and security. However, limited evidence exists on how such communities perceive. This study examined how community perceptions, lived experiences, and adaptive responses to climate change in a vulnerable coastal village in Odisha. Methods: A qualitative study was conducted in Penthakata, a coastal fishing village in Puri district, Odisha, between August and November 2023. 27 residents aged 50 years and above were purposively sampled. Data were collected through in-depth interviews and analysed using Framework Analysis approach to identify themes. Results: Participants perceived clear climatic shifts, including more frequent and intense cyclones, irregular rainfall, and rising temperatures. Extreme events caused extensive housing damage, food insecurity, livelihood disruptions, school interruptions, and increased waterborne, vector-borne, and heat-related illnesses. Mental health stress and major disruptions in healthcare access were common. Fishers reported declining near-shore fish, deeper-sea fishing, and economic instability. Misconceptions and religious attributions shaped climate and disease understanding. Limited relief, inconsistent compensation, and interstate welfare ineligibility substantially heightened vulnerability. Conclusions: Climate impacts are shaped by the interaction of environmental exposure, livelihood fragility, cultural beliefs, health-system limitations, and structural governance barriers. Interstate welfare ineligibility emerged as a critical but overlooked determinant of vulnerability. Strengthening climate literacy, culturally aligned health communication, service preparedness, compensations, and social protection access is essential.